Data for: The Spatial Resolution Enhancement for a Thermogram Enabled by Controlled Sub-pixel Movements - Zhao, Yifan; Dai, Weixiang; Addepalli, Pavan (Cranfield University, 2019)
The measurement accuracy and reliability of thermography is largely limited by a relatively low spatial resolution of the thermal imager. Using a high-end camera to achieve high spatial resolution can be costly or infeasible due to a high sample rate required. Furthermore, the system miniaturisation becomes an inevitable trend with the continuous development of Internet of Things and their suitability to in-situ inspection scenarios. However, a miniaturised sensor usually suffers a low spatial resolution. Addressing this challenge, the paper reports a novel Spatial Resolution Enhancement for a Thermogram (SRE4T) system to significantly improve the spatial resolution without upgrading the sensor. A high-resolution thermal image is reconstructed by fusing a sequence of low-resolution images with sub-pixel movements. To achieve the best image quality, instead of benefiting from natural movements of existing studies, this paper proposes to use a high-resolution xy translation stage to produce a sequence of controlled sub-pixel movements. The performance of the proposed system was tested on both high-end and low-end thermal imagers. Both visual and quantitative results successfully demonstrated the considerable improvement of the quality of thermal images (up to 30.5% improvement of peak signal to noise ratio). This technique allows improving the measurement accuracy of thermography inspection without upgrading sensors. It also has the potential to be applied on other imaging systems.
Keywords: 'Resolution Enhancement'; 'NDT'; 'Motion Estimation'; 'Image Reconstruction'; 'Control Systems; Robotics and Automation'